An internal electron reservoir enhances catalytic CO2 reduction by a semisynthetic enzyme. Issue 64 (13th July 2016) - Schneider, Camille R.; Shafaat, Hannah S.
Abstract : An artificial metalloenzyme construct has been developed that performs light-driven and electrocatalytic CO2 reduction. Abstract : The development of an artificial metalloenzyme for CO2 reduction is described. The small-molecule catalyst [Ni II (cyclam)] 2+ has been incorporated within azurin. Selectivity for CO generation over H + reduction is enhanced within the protein environment, while the azurin active site metal impacts the electrochemical overpotential and photocatalytic activity. The enhanced catalysis observed for copper azurin suggests an important role for intramolecular electron transfer, analogous to native CO2 reducing enzymes.